Metal-free aza-Claisen type ring expansion of vinyl aziridines: an expeditious synthesis of seven membered N-heterocycles. Issue 12 (15th January 2019) - Singh, Deepak; Ha, Hyun-Joon
Abstract : A metal-free approach for the synthesis of 7-membered aza-heterocycles has been developed by the intermolecular [5 + 2] cycloaddition of non-activated vinylaziridines and alkynes. Abstract : A metal-free approach for the synthesis of 7-membered aza-heterocycles has been developed by the intermolecular [5 + 2] cycloaddition of non-activated vinylaziridines and alkynes. This method has a broad substrate scope under mild reaction conditions to afford structurally diverse 7-membered N-heterocycles in high yield up to 92%.